Interactive online learning support: Progress on research to date - Quinton, Stephen (IEEE, 2007)
This paper reports on progress to date in relation to along term research project underway at Curtin University ofTechnology. The project aims to devise tools that interactivelysupport the cognitive learning processes of today?s knowledgeworkers as exemplified by researchers, managers and students.The empowering tools alluded to here are not simply intended tomanage, calculate, search, order and arrange search results as isoften the case with current search systems. Instead, the project isconcerned with applying semantic analysis techniques,specifically the Normalised Word Vector (NWV) technologydeveloped at Curtin to the construction of a range of ?intelligent?online cognitive support tools. The goal is to devise a system thatenhances learners? cognitive functioning by augmenting thehuman intellect to achieve greater capacity to conceptualise andultimately, construct new knowledge.